VD_FINDINFO Jug / 2017 / 269 vom 20. März 2017 - VD Tribunal cantonal (2017)
MISE EN DANGER DE LA VIE D'AUTRUIART. 129 CP, FIXATION DE LA PEINE, TRAITEMENT AMBULATOIRE | 129 CP, 47 CP, 63 al. 1 CP, 63 al. 2 CP, 63a al. 3 CP